Strategi Pemanfaatan Media Sosial Sebagai Sarana Promosi Sekolah Musik Di Dotodo Music Edutainment - Manurung, Joice; Anom, Erman; Iswadi (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2023)
ABSTRACT The purpose of this study was to find out how the efforts to use social media as one of the strategies and means of promoting music schools were carried out by Dotodo Music Edutainment. The research method used in this study is a qualitative research method with a case study type. The choice of this type of case study is because the researcher will understand in depth the context, process, and complexity of the phenomenon being studied. The location of this research is at the Dotodo Music Edutainment music school, which is in the city of Bandung. In the process of collecting data, researchers used interview and observation techniques. Interviews were conducted with the two founders, who are also the owners and teaching staff at the music school. The results of the research conducted show that Dotodo Music Edutainment utilizes several types of social media such as Instagram, Facebook and TikTok to reach a wider audience and school promotions. By presenting interesting and relevant content, and involving students in the marketing process, Dotodo Music Edutainment builds a strong brand image and raises public awareness about a quality music school. Dotodo Music Edutainment also uses other supporting strategies such as distributing brochures. This gives the impression of a strong traditional approach and is basically still effective. Keyword: Social-media, Promotion, Dotodo Music Edutainment